Characterization Of Precipitates In Structural Titanium Microalloyed Steel By Transmission Electron Microscopy And High Resolution (HRTEM) - L. Béjar-Gómez (The Minerals, Metals and Materials Society, 2006)
The aim of this research work is to study and characterize precipitates in structural microalloyed steel by transmission electron microscopy and analysis by high resolution (HRTEM). Microalloyed steel with titanium was produced by casting in an electrical induction oven of 25 Kg. capacity. Carbon content in steel was less than 0.1 % and titanium content of 0.04%. Steel was processed thermomechanically; reheated to 1250ºC and hot rolled on a laboratory mill to a 13.0 mm thick plate with a finish rolling temperature of 900ºC and thickness reduction of 80%. Analysis by High Resolution Transmission Electron Microscopy (HRTEM) identified precipitates in the steel; type and morphology. Energy Dispersive Spectroscopy (EDS) analysis was applied to obtain the chemical composition of precipitates and the matrix. STEM-EDS analysis was also applied to obtain the element profile of precipitates. The results showed the presence of carbonitride precipitates of titanium, Ti (CN), with a circular morphology and size of 10 nm and less.